FUTURE OF MARKETING INTENT TO ACTION: INVESTIGATING CONSUMER’S ONLINE & OFFLINE BUYING PATTERNS, ILFORD UK - Zohaib, Muhammad; Ismail, Muhammad; Zaineb, Ambreen; Tahir, Muhammad Yasir; Tazin, Fariha (International Journal of Marketing Research Innovation, 2024)
The complicated retail environment brought forth by the growing confluence of online and offline channels calls for a better comprehension of customer impulse buying patterns. The tendency of the consumers for unplanned and spontaneous shopping was the core purpose of finding out through this study, from the United Kingdom consumer’s perspective. To dig-out the propensity of the consumers towards online and offline buying habits and planning. This study is based on a qualitative approach by using ‘desk methodology’ We’ve collected 146 articles/studies via web browsing, and selected core 44 article’s (secondary data), which enhances understanding of the consumer’s impulsive buying decisions specifically in Ilford., a suburban field, in East London. This study uses thematic analysis to shine a light on the dynamics of impulse purchases differently in online and offline contexts due to, among other factors, sensory experience for groceries but not fashion vs. convenience. Results showed that happy consumers are more inclined to make spontaneous purchases. While offline impulse purchases are tied to sensory and in-store elements. Ilford (UK) based consumers are very conscious about their time and desired products. They spend their time only on those buyings which are very essential in their daily routine. For the rest of things, they preferred to buy online. The major findings of this study exhibit that channel-specific strategies are crucial for businesses since consumers’ impulse buying habits differ in online and offline settings and demonstrate that retailers to shift their marketing strategies to account for the distinct features of every channel. JEL Classification Codes: M31, M37, D12.